Psychometric properties of the Chinese version of the health behavior motivation scale: a translation and validation study - Ge, Yuanhui; Zheng, Chen; Wang, Xin; Liu, Tao (Frontiers in Psychology, 2024)
Objective:This study's objectives were to translate the Health Behaviour Motivation Scale (HBMS) into Chinese and verify the scale's validity and reliability among Chinese healthy adults.The HBMS scales were translated into Chinese based on Brislin's principles. The Chinese version of HBMS is created through translation, back translation, and cross-cultural adaptation.This investigation implemented the convenience sampling method to conduct a survey on 781 healthy respondents, utilizing the Chinese version of the HBMS and a general demographic questionnaire.We used AMOS (v28.0) and SPSS (v26.0) for statistical analysis. We employed test-retest reliability, split-half reliability, and internal consistency to assess the reliability of the translation questionnaire.Structure validity and content validity were used to assess validity.The Chinese version of the Health Behavior Motivation Scale (HBMS) had a Cronbach's alpha coefficient of 0.885, and the range of Cronbach's alpha values for each dimension was 0.820-0.885. The scale's test-retest reliability was 0.824, and its split-half reliability was 0.906. Five public factors with a cumulative variance contribution of 56.527% were retrieved from the exploratory factor analysis. Moreover, the factor loading value for each item exceeded 0.4.In confirmatory factor analysis, the indicators were reported as follows: χ²/df = 1.567, GFI = 0.900, CFI = 0.952, IFI = 0.952, TLI = 0.946, AGFI = 0.881, PGFI = 0.757, PNFI = 0.789, RMSEA = 0.039, and the results of the model fit metrics were within the reference range.The Chinese version of the HBMS exhibits strong discrimination, validity, and reliability. The tool effectively identifies the motivation of healthy people to engage in healthy behaviors. It can be used by healthcare practitioners to assist in the development of follow-up interventions to reduce the prevalence of chronic disease in older people and the incidence of chronic disease in populations of young and middle-aged people.